Data warehousing in the age of big data - Krishnan, Krish (Morgan Kaufmann is an imprint of Elsevier, 2013)
This book will help you navigate through the complex layers of Big Data and data warehousing while providing you information on how to effectively think about using all these technologies and the architectures to design the next-generation data warehouse.